PRODUCTION CONTROL UNDER PROCESS QUEUE TIME CONSTRAINTS IN SYSTEMS WITH A COMMON DOWNSTREAM WORKSTATION - Chen, Yu-Ting; Wu, Cheng-Hung; Tien, Yin-Jing; Yu, Cheng-Juei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
This research develops a dynamic scheduling method for multi-product production systems under process queue time (PQT) constraints, wherein waiting time between consecutive processing steps is constrained by predefined upper limits. If the waiting time of a work-in-process (WIP) violates the corresponding PQT constraint, the WIP may be scrapped or the yield quality will deteriorate seriously. When machines are unreliable, random machine failures cause high cycle time variance and significantly increase the risk of violating PQT constraints. Therefore, for production systems with PQT constraints, a robust dynamic scheduling method with real time machine reliability considerations is critical. In this research, multi-product production systems with a common downstream workstation are considered. PQT constraints before the downstream workstation are assumed. The Markov decision process model is developed to address production control problems, and the objective is to minimize total expected waiting and scrap costs. Simulation results show the robustness of the proposed control method. On average, the proposed method reduces production costs by 20% and improves system throughput by 2%.